Involvement of Lanthanides in the Free Radicals Homeostasis - Valcheva-Traykova, Maria; Saso, Luciano; Kostova, Irena (Current Topics in Medicinal Chemistry, 2014)
Lanthanides are group of rare-earth elements with growing applications both in the industry and healthcare. Their unique properties impose various possibilities for involvement in electron transfer reactions essential for the cellular survival and health on general. The intensified contact of people with lanthanides and the expanding medicinal applications of their compounds insist more profound knowledge on the involvement in biologically relevant electron transfer reactions. It is well known that the balance between formation and elimination of free radicals in a living body is essential for its health and survival. Any internal or environmental factor that alters this balance alters the homeostasis and this way altering the health status. In the present review, the possibilities of changing the balance between formation and elimination of free radicals, due to introduction of different lanthanides and their complexes with organic ligands, were explored, based on the available information in the literature. It was observed that lanthanides may act either as antioxidants or pro-oxidants, depending on the environment, the nature of the bonding in their compounds, and concentration in the tissues. The opportunities for their application in medicine were related with the abilities to control over their involvement in the overall oxidative status of the body.
Keywords: Lanthanides